Find the second, fourth and eleventh terms of the sequence described by the rule. A(n)=3+(n - 1)(5)

A(2)=

3 answers

Find the second, fourth, and eleventh terms of sequence described by the rule.
A(n) = 3 + (n - 1)(5)
--------------------------------
A(n) = 3+ (n-1)5
A(2) = 3 + (2 - 1) × 5
A(2) = 3 + 1 × 5
A(2) = 3 + 5
A(2) = 8

Next, I had to find A(4)= ?
So what, I did was:

A(n) = 3 + (n - 1)5
From A (4), n = 4
A(4) = 3 + (4 - 1) × 5
A(4) = 3 + 15
A(4) = 18

However now, I need to find A(11) = ?
Please help me find A(11) = ?
you're kidding, right? You did n=2 and n=4, but can't figure out how to do n=11?
Just follow the same steps.
I just figured it out. You know we all learn differently so, I'd suggest you should've thought about that first. Otherwise thanks for the very helpful comment.